2004
DOI: 10.1007/s00397-004-0403-6
|View full text |Cite
|
Sign up to set email alerts
|

Shear-induced aggregation and break up of fibril clusters close to the percolation concentration

Abstract: IntroductionStructural changes of complex fluids under steady shear flow were investigated for different type of materials, such as suspensions, associating polymers and polymer solutions [1,2,3,4,5,6]. Under specific conditions, depending on the material, a shear-thickening regime is observed followed by shear-thinning behaviour [3,4,6]. Shear-thickening is often the result of shear-induced formation of intermolecular structures (clusters), leading to an increase in the effective volume fraction [1,2,3,5,7]. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Recently, it was found that β-Lg can form fibrils on heating treatment at low pH, on heat treatment under high pressure, or in the presence of organic solvents , . Many studies on the mechanism of fibril formation and on the building blocks of fibrils have been carried out , . Akkermans et al claimed that rather than denatured intact proteins, the building blocks of β-Lg fibrils are peptides obtained through acid hydrolysis of β-Lg molecules on heat treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was found that β-Lg can form fibrils on heating treatment at low pH, on heat treatment under high pressure, or in the presence of organic solvents , . Many studies on the mechanism of fibril formation and on the building blocks of fibrils have been carried out , . Akkermans et al claimed that rather than denatured intact proteins, the building blocks of β-Lg fibrils are peptides obtained through acid hydrolysis of β-Lg molecules on heat treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that heat treatment results in long, straight, flexible amyloid-like fibrils at a pH lower than the isoelectric point (e.g., pH 2–3), whereas only short, curly aggregates are formed at high pH (higher than the isoelectric point, e.g., pH > 7). During the past decade, many studies to understand the mechanisms of fibril formation and to identify the building blocks of fibrils have been carried out. Using atomic force microscopy, Radford and co-workers attempted to achieve detailed understanding of the formation of amyloid fibrils from β 2 -microglobulin at different protein concentrations, pH values, and ionic strengths. This group found two distinct competitive pathways for fibril formation as well as heterogeneity of the amyloidal assembly .…”
Section: Introductionmentioning
confidence: 99%